Foregrounding the Muslim periphery (Respond to this article at http://www.therai.org.uk/at/debate). Issue 4 (25th July 2013) - Benthall, Jonathan
<x xml:space="preserve">Abstract</x> This guest editorial considers the implications of Akbar Ahmed's latest book –The Thistle and the Drone: How America's war on terror became a global war on tribal Islam, which was the centrepiece of several panel discussions in London.